New data on African health professionals abroad - Clemens Michael A; Pettersson Gunilla (BMC, 2008)
Abstract Background The migration of doctors and nurses from Africa to developed countries has raised fears of an African medical brain drain. But empirical research on the causes and effects of the phenomenon has been hampered by a lack of systematic data on the extent of African health workers' international movements. Methods We use destination-country census data to estimate the number of African-born doctors and professional nurses working abroad in a developed country circa 2000, and compare this to the stocks of these workers in each country of origin. Results Approximately 65,000 African-born physicians and 70,000 African-born professional nurses were working overseas in a developed country in the year 2000. This represents about one fifth of African-born physicians in the world, and about one tenth of African-born professional nurses. The fraction of health professionals abroad varies enormously across African countries, from 1% to over 70% according to the occupation and country. Conclusion These numbers are the first standardized, systematic, occupation-specific measure of skilled professionals working in developed countries and born in a large number of developing countries.